Structures of folding intermediates on BAM show diverse substrates fold by a conserved mechanism - Benjamin D. Thomson; Melissa D. Marquez; Shaun Rawson; Thiago M. A. dos Santos; Stephen C. Harrison; Daniel Kahne (Proceedings of the National Academy of Sciences, 2026)
The outer membranes of mitochondria, chloroplasts, and Gram-negative bacteria contain β-barrel membrane proteins that are assembled by conserved multisubunit machines. In bacteria, the β-barrel assembly machine (BAM) folds over a hundred compositionally different substrates into barrels that vary greatly in size. Some larger barrels require globular proteins to plug the barrel lumen. How a single machine can assemble such different barrels is unknown. Here we report three structures representing progressively folded stages of a 16-stranded barrel engaged with BAM, as well as the structure of a late-stage folding intermediate of a 26-stranded substrate folding around its soluble lipoprotein plug on BAM. We find that BAM catalyzes folding of these substrates by a uniform mechanism in which BAM undergoes major distortions to accommodate the nascent barrel.